Bright angles of positivity in the Prophet’s biography= Sudut cerah positiviti dalam biografi Rasulullah - Mohammad Hassan Hilal , Huda (International Islamic University Malaysia, 2014)
The topic of positive thinking in the recorded biography of the Prophet (s.a.w.) has not been investigated as much as it deserves, since the topic of positivity in general is hard to find. A quite few researches on positivity from Islamic approach have been done in the light of modern human knowledge. This research seeks to prove the assumption that the Prophet MuÍammad (s.a.w.) advanced a distinct multidimensional positive pattern, spiritual, emotional, moral and religious that reflected in his personality, his behavior and his teachings, by adopting an analytical methodology in tracing his sayings and deeds in old transcripts. This effort is aimed at filling the lacuna between Islamic heritage and contemporary researches, clarifying the Prophet’s (s.a.w.) positivity with his family, his companions and non-Muslims, and displaying the plethora of effects of his positivity on cross-religious, and psycho social settings.